Standard guidelines for bill of quantities customised for building conservation works: The Malaysian context / Lim Yoke Mui - Lim, Yoke Mui (2017)
The aim of this research is to formulate a guideline for preparing Bill of Quantities (BQ) for building conservation works. The justifications for this research are derived from both the practical and the academic angle. Anecdotal feedback from the conservation industry claims that the variance between tender prices of conservation projects is very high and this issue poses difficulty in the awarding of contracts. In any tender pricing, BQ is the most important part of the tendering process. Thus, the issue of tender pricing requires research on the BQ document itself. While the subject pertaining to BQs has been researched since the 1960s covering various areas such as type, use, format, pricing, reliability and relevance of the BQs; all these studies focused on new building works and not conservation works. Thus the reason for the high variance in conservation tenders is still unknown yet the rising interest in conservation works in this country has created the need to improve the area of tender pricing for the conservation industry. Qualitative research approach is used in this study and the reason is due to the situation and character of the conservation industry where data are still scarce and there are still many unknowns pertaining to tender pricing for conservation works. In order to uncover and probe deeper into the issues faced by these tenderers, semi-structured interviews are conducted with conservation contractors. Data from the interviews are analysed using the thematic analysis method. The findings revealed that hidden works, inexperience in the conservation industry, various issues with the BQ preparation, as well as labour and material costs are the major reasons for the variance in tenders for conservation projects. The interviews also revealed the inadequacies of the current tender documents which were then categorised into three categories namely BQ, Specification and Documents other than BQ. The data also identified items that had no effect on pricing. Suggestions from the interviews formed the basis for the proposed guidelines which were then validated under four sections namely Guidelines for Preliminaries Bill, Measured Work Bill, P.C. & Provisional Sum Bill and Documents other than BQ. Considering the impossibility of testing the guidelines in the industry during the research period yet the proposed guidelines needed validation, this study used the 2-round Delphi survey method to obtain feedback from industry experts on the feasibility and viability of the guidelines. Feedback from the 2-round Delphi survey are then used to revise and improve the proposed guidelines to derive to its final version proposed in this research. It is hoped that the proposed guidelines will be used by quantity surveyors as reference in the preparation of tender documents for building conservation projects in the immediate future.